Beyond Resources, Beyond Technologies, Beyond One's Institution: Developing New Productive Forces for Knowledge Services through Reform and Innovation of Traditional Knowledge Service Mechanisms - Xiaolin ZHANG (Nongye tushu qingbao xuebao)
[Purpose/Significance] AI technology has brought unprecedented challenges and opportunities to the knowledge service industry, requiring innovation and reform of knowledge services in various dimensions, including technology, organizational mechanisms, and service models, to adapt to the development of emerging knowledge productivity. AI technology has not only changed the way knowledge is produc ed and disseminated, it has also significantly influenced the processes by which users acquire knowledge and the systems through which they produce knowledge. Simply promoting the empowerment of knowledge services through AI from a technical point of view is not enough to achieve the transformation and upgrading of knowledge service institutions. [Method/Process] This article begins with the multi-level transformative impact of AI technology on emerging knowledge productivity, proposing that generative AI has rapidly become a powerful new force in knowledge production, and that AI agents are gradually becoming revolutionary tools for the flexible design and innovation of complex processes. We argue that the rapid development of AI has deepened the connotations and forms of AI empowerment. The article further explores the barriers in production relations in the development of new quality productive knowledge services and examines the challenges of aligning traditional knowledge services with user knowledge processes and user production systems in the AI environment. We propose to promote the development of the knowledge service industry through multi-level AI empowerment and innovation of the traditional organizational mechanisms of knowledge services. The article emphasizes placing the construction of new production relations at the key point of AI empowerment, developing new user-oriented, user-process-driven knowledge service organizational models, and developing new docking logic and service embedding architectures between knowledge services and user production systems, as well as building user-oriented, service-driven internal organizational models. Specifically, we present possible new directions for knowledge service production relations, such as the Library-Inside model, the Inside-Out+Outside-In model, new docking architectures between knowledge services and user production systems, and reforms in internal organizational models of institutions. [Results/Conclusions] By exploring the multi-level transformative effects of AI technology and analyzing the barriers in the production relations of new quality productive knowledge services, this article proposes to reform and innovate the production relations of knowledge services. In order to promote the development of new quality productive knowledge services, we summarize the construction ideas of new-type knowledge service production relations, aiming to sustainably promote the development of new quality producitve knowledge services in the process of improving users' knowledge productivity and promoting the high-quality development of users' production systems.